A study on user operation strategies and user engagement enhancement methods for fitness App: A case analysis of Keep - Zhang Liyu (SHS Web of Conferences)
With the enhancement of national health awareness and the improvement of physical fitness demand, the continuous popularization of mobile devices and the continuous improvement of their performance, online fitness has become a popular form of exercise in the current era, and mobile applications have become a tool to assist exercise for many people, Keep is one of many sports fitness apps. The purpose of this study is to explore the user operation strategy of sports application KEEP and the methods to enhance user stickiness. It will assess the effectiveness of these approaches and strategies and analyze their strengths and areas for improvement. Finally, the research will provide practical suggestions and future prospects for further improving user engagement and application performance. This study will mainly use the literature research method and interview method to provide information for this study. Finally, the findings show that Keep increases user engagement by using different creative approaches.